Studies on conservation and management of coastal resources through the integration of social, physical and biological approach: case study in Paojepe, Wajo, South Sulawesi - Y. Purwanto (Journal of Tropical Ethnobiology, 2005)
This research is based upon an interdiciplinary field study encompassing anthropology, biology, and oceanography, conducted within a period of May 1999 to May 2001 at Paojepe coast, Wajo regency in South Sulawesi. The study has three main objectives : firstly, to identify social, cultural, ecological/biological and econo-demographic problems that concerned mangrove-forest conversion phenomenon into brackish water milkfish pond areas, as one of the main economic activities of the local people. Secondly, to identify achievements as well as failures in the efforts to rehabilitate mangrove forest by using of analyzing social, ecological and demographic symptoms and conditions at the coast of Paojepe. Thirdly, to identify the potentials of social institutions the people of Paojepe maintain, which was believed to be able to contribute as the means and medium in the efforts to apply the most suitable intervention strategies in coastal management, particularly intervention strategies in rehabilitation of the mangrove forests. The study on biological aspect has identified the biological diversity of Paojepe coast and also identified on the on-going ecosystem changes as consequences of mangrove depletion, coastal abrasion, and coral reef mining. The results of the oceanographic observation on Paojepe coast showed that, the sea currents That parallel the shore can move at speed of 62.64 cm/second and many transport suspended sediment and/or other materials from the coats heading offshore at a depth of 19 to 20 m, approximately 1333.4 m from the shore. The effect of rising and falling tide on coastal abrasion is followed by the presence of huge waves, especially at high tide. Coral reef has still been mined by the community. At a contour depth of about 4 meters, the reef could actually be a natural protector from the sea wave attacks on the eastern coast of Paojepe. The coral reef mining has resulted in their disappearance, sea waves hit the shore directly and frontally. The result of social study have tapped in aspirations of most of the local people, who have begun to be aware of the danger of abrasion on their locations, These people have begun to realize that abrasion can in fact pose serious threats to their economy, as more and more ponds located on the beach have been eroded. This means potential reduction on their milkfish and shrimp commodities. As have been empirically observed, owners of such ponds have strong. motivation in mangrove re-plantation. They have even more considered to plantation of Rhitopbora spp. on their ponds. The multidiciplinary approaches in the conservation and management will be discussed later in this paper.